2016
DOI: 10.1088/0957-0233/27/12/125101
|View full text |Cite
|
Sign up to set email alerts
|

A method enabling simultaneous pressure and temperature measurement using a single piezoresistive MEMS pressure sensor

Abstract: In this paper we present a high-performance, simple and low-cost method for simultaneous measurement of pressure and temperature using a single piezoresistive MEMS pressure sensor. The proposed measurement method utilizes the parasitic temperature sensitivity of the sensing element for both pressure measurement correction and temperature measurement. A parametric mathematical model of the sensor was established and its parameters were calculated using the obtained characterization data. Based on the model, a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A piezometer based on MEMS technology particularly piezoresistive sensors may improve cost and energy consumption as well as accuracy and ease of installation compared to traditional monitoring equipment. It is reported that using parametric mathematical model it is possible to measure temperature and pressure in piezoresistive sensors simultaneously with little or no additional hardware and without affecting the pressure measurement performance [148]. This may be use as a reference measurement for verifying of potentially faulty readings from other temperature sensors, an astonishing feature of this device.…”
Section: Pressure Monitoringmentioning
confidence: 99%
“…A piezometer based on MEMS technology particularly piezoresistive sensors may improve cost and energy consumption as well as accuracy and ease of installation compared to traditional monitoring equipment. It is reported that using parametric mathematical model it is possible to measure temperature and pressure in piezoresistive sensors simultaneously with little or no additional hardware and without affecting the pressure measurement performance [148]. This may be use as a reference measurement for verifying of potentially faulty readings from other temperature sensors, an astonishing feature of this device.…”
Section: Pressure Monitoringmentioning
confidence: 99%
“…Ideal for electric field measurement sensors. MEMS sensors have significant application effects in the fields of temperature detection (Ando et al, 2011;Frantlovic et al, 2016), pressure measurement (Nag et al, 2020;Sahay and Jindal, 2021), and humidity detection (Chen et al, 2016;Zhao et al, 2021), and are gradually becoming the development direction and research focus of electric field sensors. At present, the miniature electric field sensor based on MEMS technology is mainly based on the resonant structure of the charge sensing principle (KAINZ et al, 2018;Shanhong et al, 2021), All induction designs have shield plates moving above the induction electrode and shielding electrode by moving laterally.…”
Section: Introductionmentioning
confidence: 99%